2015
DOI: 10.5194/acp-15-3671-2015
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous reductions in emissions of black carbon and co-emitted species will weaken the aerosol net cooling effect

Abstract: Abstract. Black carbon (BC), a distinct type of carbonaceous material formed from the incomplete combustion of fossil and biomass based fuels under certain conditions, can interact with solar radiation and clouds through its strong light-absorption ability, thereby warming the Earth's climate system. Some studies have even suggested that global warming could be slowed down in the short term by eliminating BC emission due to its short lifetime. In this study, we estimate the influence of removing some sources o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 52 publications
1
16
0
Order By: Relevance
“…The aerosol reduction will weaken the aerosol net cooling effect and produce an additional warming of the Earth's climate system (Shindell et al 2008;Wang et al 2015a), thus affecting future extreme temperature and precipitation events. Our results show that reduced aerosol emissions will lead to marked increases in TXx, TNn, and TR over China.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aerosol reduction will weaken the aerosol net cooling effect and produce an additional warming of the Earth's climate system (Shindell et al 2008;Wang et al 2015a), thus affecting future extreme temperature and precipitation events. Our results show that reduced aerosol emissions will lead to marked increases in TXx, TNn, and TR over China.…”
Section: Discussionmentioning
confidence: 99%
“…To mitigate environmental pollution and the resulting impacts on human health, governments worldwide will likely take continuous and stringent measures to reduce the emissions of most anthropogenic aerosols and their precursors during the twentyfirst century. This will result in gradual decreases in atmospheric aerosol concentrations and the net cooling effect of aerosols in the future (i.e., contributing to an additional warming) (Shindell et al 2008;Wang et al 2015a). Sillmann et al (2013b) showed that future reduction in aerosol emissions could greatly enforce the warming effect due to GHG and increase the temperature and precipitation extremes in Europe.…”
Section: Introductionmentioning
confidence: 98%
“…Zhang et al (2012Zhang et al ( , 2014, and Wang et al (2014). The performance of the model has been evaluated by Wang et al (2014), Zhang et al (2014), and Wang et al (2015) in detail. They demonstrated that the model has a good ability to simulate aerosols, cloud properties, and meteorological fields.…”
Section: Introductionmentioning
confidence: 99%
“…GHGs and aerosols will continue to be the two most important anthropogenic forcing agents in the 21st century [Myhre et al, 2013]. The expected declines of anthropogenic aerosols in the 21st century from present-day levels would impose an additional warming on the Earth [Rotstayn et al, 2013;Wang et al, 2015;Lin et al, 2015], which will aggravate the climate extremes caused by GHGs-induced warming Wang et al, 2016a]. Separating the contributions by different forcing agents to extreme precipitation increases under different emission scenarios would be beneficial to policy-making on climate mitigation and adaptation.…”
Section: Introductionmentioning
confidence: 99%